2008
DOI: 10.1007/s11120-008-9334-x
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress inhibits photosystems II and I in cyanobacteria

Abstract: Recent studies of responses of cyanobacterial cells to salt stress have revealed that the NaCl-induced decline in the photosynthetic activities of photosystems II and I involves rapid and slow changes. The rapid decreases in the activities of both photosystems, which occur within a few minutes, are reversible and are associated with osmotic effects, which induce the efflux of water from the cytosol through water channels and rapidly increase intracellular concentrations of salts. Slower decreases in activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 69 publications
9
99
0
Order By: Relevance
“…The second step involved the transfer of aminoacyl of the t-RNA. Phycobillisomes are the major light harvesting complexes of cyanobacteria under nitrogen fixing condition and under salt stress conditions; major component of the phycobilisomes is strongly expressed [36,59]. The above findings are in agreement with our interpretations.…”
supporting
confidence: 89%
“…The second step involved the transfer of aminoacyl of the t-RNA. Phycobillisomes are the major light harvesting complexes of cyanobacteria under nitrogen fixing condition and under salt stress conditions; major component of the phycobilisomes is strongly expressed [36,59]. The above findings are in agreement with our interpretations.…”
supporting
confidence: 89%
“…Preparation of growth medium with added calcium N t = N 0 ·e rn·t [1] Where N t is the number of cells in time t; N 0 is the initial number of cells; and r n is the growth rate (33).…”
Section: Methods Strain Maintenancementioning
confidence: 99%
“…As a further indicator of the potential importance of salinity in defining microbial mat and microbialite communities, salt stress has been shown to inhibit the photosynthetic capability of cyanobacteria (Allakhverdiev and Murata, 2008;Hagemann, 2011), which may further explain these metagenomic differences observed. Furthermore, it has been suggested that Pavilion Lake microbialite heterotrophs contribute to the cementation process of thrombolites by subsequent in-filling of microstructures (Omelon et al, 2013), a process that could potentially be occurring in Shark Bay systems.…”
Section: Stress Responsementioning
confidence: 99%